2020
DOI: 10.34154/2020-ejcs-0201-20-26/euraass
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Itch/p73 pathway by thymoquinone as a novel therapeutic strategy for cancers with p53 mutation

Abstract: The tumor suppressor p73 is a member of p53 family and has a high degree of similarity with p53 function and structure. Like p53, p73 can also induce the expression of several genes involved in cell cycle and apoptosis. p73 expression is downregulated in many tumors by several mechanisms including the ubiquitination pathway. Thus, understanding the ubiquitin-proteasome pathway in p73 regulation will help in targeting this later and develop a new promising therapeutic strategy for cancer with p53 mutations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…This inhibition is due to compromised 20S proteosomes complex functionality and not to downregulation of its synthesis as observed through western blotting and 20S proteosomes activity analysis. In addition, E3 ubiquitin ligase was also downregulated with thymoquinone treatment in acute leukemia model ( Alghamdi et al, 2020 ). Based on this evidence in cancer subject and with the importance of autophagy in the eye, study on thymoquinone in proteosome might provide a novel mechanism of thymoquinone in ocular disease application.…”
Section: Effects Of Thymoquinone On Signaling Mechanisms Of Ocular Ne...mentioning
confidence: 99%
“…This inhibition is due to compromised 20S proteosomes complex functionality and not to downregulation of its synthesis as observed through western blotting and 20S proteosomes activity analysis. In addition, E3 ubiquitin ligase was also downregulated with thymoquinone treatment in acute leukemia model ( Alghamdi et al, 2020 ). Based on this evidence in cancer subject and with the importance of autophagy in the eye, study on thymoquinone in proteosome might provide a novel mechanism of thymoquinone in ocular disease application.…”
Section: Effects Of Thymoquinone On Signaling Mechanisms Of Ocular Ne...mentioning
confidence: 99%
“…Itch E3 ubiquitin-protein ligase (Itch) has been reported to be highly expressed in several tumors, including lung cancer, breast cancer, pancreatic cancer, skin cancer, and neuroblastoma, and its inhibition leads to the induction of apoptosis and the inhibition of cell proliferation [ 38 , 59 , 62 , 63 , 64 ]. Itch selectively binds and ubiquitinates p73α via the PY motif (Met 452–Ala 489) but not p53, thereby leading to a proteasome-dependent p73 degradation [ 43 ].…”
Section: Ubiquitination-dependent P73 Inhibitionmentioning
confidence: 99%
“…We and others have shown that thymoquinone (TQ), the bioactive compound of black seed oil, has inhibitory effects on several cancers through the targeting of several signaling pathways [ 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 , 159 ], including the reactivation of the p73 protein in p53-mutated tumors [ 136 , 160 , 161 ]. Recently, TQ was proposed to increase the expression of the p73 protein in a p53-mutant acute lymphoblastic leukemia cell line (Jurkat cells) by targeting the expression of various E3 ubiquitin ligases for p73, including Itch, Mdm2, FBXO45, and TRIM32 [ 62 ]. TQ increased the expression of the p73 protein in Jurkat cells, and this effect was associated with a significant decrease in the expression of Itch in those cells, as well as in human promyelocytic leukemia HL60 cells and human triple-negative MDA-MB-468 breast cancer cells that also bear mutant p53 [ 62 ].…”
Section: Targeting Post-translational Modifications Of P73 For Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations